STUDI DESKRIPTIF NON HARMONIC TONES PADA LAGU ANAK-ANAK KARYA A.T. MAHMUD - Ari Berli Kuswara; Yensharti Yensharti; Jagar Lumban Toruan (SENDRATASIK UNP, 2013)
Abstract This research aimed at decribing the non harmonic tones found in 3 children songs composed by A.T. Mahmud. The song were “Bintang Kejora”, Pelangi”, and “Amelia”. The non harmonic tones were were analyzed based on the progression of three main chord (I, IV and V) in the background of the melody. According to Ottman (1961:127),non-harmonic tones may be identified and classified by relationship of dissonance (the non-harmonic tone)to the harmonic tones which precade and follow it. Based on the content analysis approach used in this research, it was found that 19 non harmonic tones (35%) in the song of “Bintang Kejora”, 8 non harmonic tones (17%) in the song of “Pelangi”, and 12 non harmonic tones (22%) in the song of “Amelia”. It was concluded that the amount of non harmonic tones within this 3 song were lower than 30%. As a result, the melody of these songs was dominated by leaping movements which was still included as fair interval for children. Keywords: children songs, A.T. Mahmud,the non harmonic tones